CNT-motor driven by competition between thermal fluctuation and REF. (1st July 2022) - Cai, Kun; Wu, Puwei; Shi, Jiao; Zhong, Zheng; Zhang, Yingyan
Highlights: We propose a model of CNT-based nanomotor driven by two methods. The bladed rotor in water is driven to rotate by the inwardly radial deviated (IRD) atoms on the stators and/or by a rotating electric field (REF). The stable rotational frequency of the rotor is controllable. Some remarkable conclusions are presented for the design of the rotary nanomotor. Abstract: Rotary nanomotors are essential components in nanomachines. This study proposes a carbon nanotube (CNT)-based nanomotor driven by two methods. In the first method, we set inwardly radial deviation (IRD) to some of the atoms at the edges of the CNT stators which confine and support the rotor tube. At finite temperatures, the IRD atoms will drive the rotor to rotate via the inter-tube collision. The other method is to apply a rotating electric field (REF) on the water box in which the bladed segment of the rotor sinks. The rotor's rotational acceleration is determined by driving moments from both the IRD atoms and or from the rotating water molecules, and the resistant moments from the environment of the rotor. Since the resistant moments increase with the rotor's rotational frequency, a stable rotational frequency (SRF) of the rotor can be obtained. Molecular dynamic simulation results demonstrate that the value of SRF depends on the number and size of the blades assembled on the rotor, the frequency of the REF, and the number of IRD atoms. This work provides a useful guideline for the design of CNT-based Brownian rotary nanomotor. Graphical Abstract: : Image, graphical abstract